Experimental Method of Fatigue Performance of Mastic Asphalt for Bridge Deck Pavement - Guilian Zou; Xiaoning Zhang; Chung Wu (The Baltic Journal of Road and Bridge Engineering)
Mastic asphalt is a type of pavement material that has good fluidity and is self-levelling at construction temperature for the bridge deck. There are highly accurate methods and indexes for evaluating fluidity and high-temperature deformation resistance for mastic asphalt-design and construction-control systems. The fatigue cracking is one of the main failure forms of bridge deck pavement. Therefore, the method used to evaluate the fatigue properties of pavement materials is also essential. The anti-deformation capability of the mastic asphalt must be increased, that results in poor fatigue performance and consequent failure of the bridge deck pavement to avoid the rutting of bridge deck pavement. In this study, a simple method is put forward for evaluating mastic asphalt fatigue performance.  Impact toughness is defined as the area under the load-displacement curve of a three-point bending beam specimen under impact load to evaluate the fatigue performance of mastic asphalt. The four-point bending beam fatigue test is used to verify the rationality of the impact toughness test method. The results showed that there is a good correlation between the impacts toughness index of mastic asphalt produced under different mixing conditions and the accumulative dissipative energy and fatigue life demonstrated by the four-point bending beam test. Therefore, to evaluate the fatigue performance of mastic asphalt by impact toughness test. Fatigue performance and rut resistance are two ways to evaluate road performance of asphalt mixtures, but they are mutually restrictive. The results show that impact toughness and dynamic stability are inversely correlated. As the impact toughness increases, dynamic stability decreases. Therefore, balancing the fatigue performance and high-temperature rutting resistance of mastic asphalt in the design and quality control is very important.